Exchange rates dynamics in a target zone: a heterogeneous expectations approach - Christian Bauer; Paul De Grauwe; Stefan Reitz (Center for Economic Studies and ifo Institute (CESifo), 2007)
The target zone model of Krugman (1991) has failed empirically. In this paper, we develop a model of the exchange rate with heterogeneous agents in a free floating and a target zone regime. We show that this simple model mimics the empirical puzzles of exchange rates: excessive volatility, fat tails, volatility clustering, and disconnection from the fundamentals. In addition, the target zone regime replicates a reduced nominal volatility for the same level of fundamental volatility as in the free floating regime and the distribution of the exchange rate within the band is hump-shaped.
Keywords: F31; F41; 330; Wechselkurs; Target Zone; Wertpapierhandel; Anlageverhalten; Agent-based Model; Theorie